2019
DOI: 10.1007/s40201-019-00363-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and exposure assessment of nitrate intake via fruits and vegetables in high and low risk areas for gastric cancer

Abstract: Background Gastric cancer (GC) is the first leading cause of cancer-related deaths in Iran. GC is a multifactorial disease and is caused by the interaction of genetic and environmental factors. The aim of this study was to assess the exposure and risk of nitrate intake through fruits and vegetables (F&V) in high-risk area (HRA) and low-risk area (LRA) of GC in Iran. Methods Twenty nine species of F&V were examined for nitrate by reverse-phase HPLC (RP-HPLC) method. Food frequency questionnaire (FFQ) data of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 38 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Presently, processed meats containing sodium nitrite are classified as Group 1 carcinogens due to sufficient scientific evidence that sodium nitrite produces the carcinogen nitrosamine (Table 1) (Ghaffari et al, 2019;Yang et al, 2019). The International Agency for Research on Cancer (IARC), a part of the World Health Organization (WHO), reported that consuming 50 g processed meat daily increased the risk of colorectal cancer by 18% (Bouvard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, processed meats containing sodium nitrite are classified as Group 1 carcinogens due to sufficient scientific evidence that sodium nitrite produces the carcinogen nitrosamine (Table 1) (Ghaffari et al, 2019;Yang et al, 2019). The International Agency for Research on Cancer (IARC), a part of the World Health Organization (WHO), reported that consuming 50 g processed meat daily increased the risk of colorectal cancer by 18% (Bouvard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%